Análise teórica da determinação do atrito de rolamento para aerodesign - Gomes, Paula Graziela Batista (Universidade Federal Rural do Semi-Árido, 2018)
The Brazilian Society of Mobility Engineers (SAE Brazil), offers annually, to engineering students and related areas, the challenge of designing and constructing an aircraft capable of carrying out a flight circuit with a payload being transported. Among the most diverse areas in the project, the landing gear is a key subsystem, being in the aircraft one of the most difficult to be designed, because it needs to have the least possible weight and at the same time mechanical resistance to withstand the loads and impacts of the same with the ground. The present research shows the study for an experimental estimation of two different bearing configurations (with and without bearing) of wheel-ground friction in landing gear applied in the AeroDesign project. For this, tests were carried out with the landing gear configuration used by the Acceptor AeroDesign Team for the SAE Brazil competition of AeroDesign 2017, in order to analyze the frictional force and its coefficient for a better performance on the aircraft at takeoff.
Monografia
Keywords: Trem de Pouso; Atrito; AeroDesign; CIENCIAS EXATAS E DA TERRA::CIENCIA E TECNOLOGIA